Reflection of women’s issues in Iraqi theatre performances - مطر ايناس (Basrah Arts Journal, 2025)
The perspective on women’s issues varies between viewing women as a value defined by customs and traditions, and recognizing their inherent abilities and real effectiveness in society. Theater emerges as a vital platform for discussing these issues, as Iraqi theatrical performances reflect the shifts in thought about women by portraying their psychological and social contradictions through multidimensional characters. Despite some symbolic progress in acknowledging the role of women, this recognition often remains partial and superficial. Given the importance of the topic and the complexities it raises, the impact of women’s issues—seen as characters rich in social and psychological significance—continues to shape the structure of theatrical performance.